The Effect of Eco-Friendly Packaging, Green Brand Image on Purchasing Decisions on MSME Product in West Bandung Regency - Diansyah, Nover; Astuti Pratminingsih, Sri (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study was conducted to explore the influence of eco-friendly packaging & green brand image on consumer purchasing to decisions for MSME products in the West Bandung Regency area. The study is motivated by the growing public concern for environmental issues and the increasing tendency of consumers to be more selective in choosing ecologically sustainable products, the method used is a quantitative approach through a questionnaire-based survey. A purposive method sampling was employed to select total of 120 participants, namely individuals who had experience purchasing MSME products labeled as environmentally friendly. The data obtained were subsequently analyzed through multiple linear regression to assess the extent to which each variable both simultaneously and individually influences purchasing decisions. The findings reveal that both eco-friendly packaging and environmentally conscious brand image significantly and positively affect consumer decisions to purchase products. As consumers' perceptions of these two aspects increase, the greater their likelihood of making a purchase. This fact reinforces that sustainable business strategies are not merely a form of social responsibility but also a key factor in enhancing market appeal and marketing effectiveness. The practical implications of this study encourage MSME actors to pay greater attention to packaging design that is not only aesthetically pleasing but also reflects sustainability values. Additionally, building a brand identity that demonstrates environmental concern can serve as a strong and relevant differentiation strategy in responding to the evolving preferences of modern consumers who are increasingly aware of green issues).